PENGARUH PERMAINAN MENYUSUN BALOK TERHADAP KEMAMPUAN MEMBILANG ANAK USIA 4-5 TAHUN DI TK. SEJAHTERA DUSUN MANCENG, DESA LARANGAN LUAR, KECAMATAN LARANGAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - mabtuhah mabtuhah; M. Ridlwan; Ratno Abidin (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine the effect of the game of arranging blocks on the ability to count children aged 4-5 years in Kindergarten. Prosperity of Dusun Manceng, Larangan Luar Village, Larangan District, Pamekasan Regency for the 2021/2022 Academic Year. And aims to find out the basics of learning to number so that in time children will be better prepared to take numeracy lessons at the next more complex level. The research method used in this study uses quantitative methods. With the technique of collecting data by interview. observation, and documentary studies. The results obtained in this study are the influence of the game of arranging blocks on the ability to count children aged 4-5 years in TK Sejahtera Dusun Manceng, Larangan Luar Village, Larangan District, Academic Year 2021/2022. In this case, the teacher must always guide and direct the child in the game of arranging blocks to stimulate the child's cognitive development so that it develops optimally according to the tasks in the stages of development. Keywords: quantitative; interview; observation; documentary study